2014
DOI: 10.4111/kju.2014.55.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Erythropoietin Administration in Patients With Prostate Cancer Undergoing Radical Prostatectomy Without Transfusion

Abstract: PurposeIn this study, we administered erythropoietin preoperatively to patients who underwent open radical prostatectomy without transfusion to increase their hemoglobin levels and investigated the efficacy of this procedure.Materials and MethodsWe evaluated 62 patients who underwent open radical prostatectomy performed by the same surgeon between June 2005 and January 2011. The 22 patients who refused transfusion were assigned to group 1; the patients who accepted transfusion were assigned to group 2. Before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Indeed, accumulating evidence proved that excess blood transfusion during surgery might not improve but even aggravated the prognosis and increased post-operative complications, especially in curative surgery for malignancies (Meng et al, 2013;Aquina et al, 2015;Diaz-Cambronero et al, 2015;Li et al, 2015;Prescott et al, 2015). Hence, oncologic surgeries without blood transfusion were developed without increased post-operative complications by means of replacement fluid administration, autologous blood infusion, parenteral iron supplement and the use of erythropoietic-stimulating agents (Lee et al, 2014;Borstlap et al, 2015;Diaz-Cambronero et al, 2015;Inoue et al, 2015). Recently, it was reported that such novel methods for blood preservation could be practical in oncologic surgeries, particularly for the selected populations such as patients with uncommon blood types or multiple RBC allo-antibodies, as well as Jehovah's Witnesses.…”
Section: (B) (A)mentioning
confidence: 99%
“…Indeed, accumulating evidence proved that excess blood transfusion during surgery might not improve but even aggravated the prognosis and increased post-operative complications, especially in curative surgery for malignancies (Meng et al, 2013;Aquina et al, 2015;Diaz-Cambronero et al, 2015;Li et al, 2015;Prescott et al, 2015). Hence, oncologic surgeries without blood transfusion were developed without increased post-operative complications by means of replacement fluid administration, autologous blood infusion, parenteral iron supplement and the use of erythropoietic-stimulating agents (Lee et al, 2014;Borstlap et al, 2015;Diaz-Cambronero et al, 2015;Inoue et al, 2015). Recently, it was reported that such novel methods for blood preservation could be practical in oncologic surgeries, particularly for the selected populations such as patients with uncommon blood types or multiple RBC allo-antibodies, as well as Jehovah's Witnesses.…”
Section: (B) (A)mentioning
confidence: 99%
“…Data were available on renal complications from 13 studies, 18,22–25,29,35,37,38,42,44,50,52 with all studies reporting no statistically significant differences between groups. Seven studies of moderate risk of bias were included in the meta‐analysis for renal complications 18,24,25,29,38,42,52 .…”
Section: Resultsmentioning
confidence: 99%
“…We collected information on the individual PBM strategies applied to manage anemia, bleeding, and coagulopathy (Table S5 to S7, Data S1). Of the 41 studies included, 26 described the application of strategies to manage anemia, 14,18,19,21,[24][25][26][27][28]30,[32][33][34][35][36][37][38][39][43][44][45]47,49,50,53,54 with a median of two strategies applied per study; 23 studies described the application of strategies to minimize bleeding, 14,[17][18][19][20][24][25][26][27][28][29][30]33,37,38,40,43,44,[47][48][49]52,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various perioperative BCSs can be used to minimize blood loss, optimize anemia tolerance, enhance hemoglobin and red blood cell production, correct coagulation defects, and promote hemostasis. These BCSs include the administration of erythropoietin, prothrombin complex concentrate, oral or intravenous iron preparations, and antifibrinolytics; preoperative autologous donation; acute normovolemic hemodilution; autologous blood transfusion after cell salvage; and use of various anesthetic techniques, such as intraoperative induction of mild hypothermia and application of permissive hypotension [14][15][16][28][29][30]. Many studies have shown that patients who refuse blood transfusion, such as JWs, can safely undergo surgery with the application of aggressive BCSs [16,[31][32][33].…”
Section: Perioperative Bcsmentioning
confidence: 99%